Scheduling and controlling production in an internet of things environment for industry 4.0: an analysis and systematic review of scientific metrological data - Tan, Lingye (2023)
To review the present scenario of the research on the scheduling and control of the production process in the manufacturing industry, this comprehensive article has extensively examined this field’s hotspots, boundaries, and overall evolutionary trajectory. This paper’s primary goal is to visualize and conduct an organized review of 5052 papers and reviews that were published between 2002 and 2022. To reveal the “social, conceptual, and conceptual framework” of the production area, identify key factors and research areas, highlight major specialties and emerging trends, and conduct research, countries, institutions, literature keywords, etc., are all used. Additionally, research methodologies are always being improved. The aim of this work is to explore more references for research implementation by analyzing and classifying the present research status, research hotspots, and potential future trends in this field of research.